The Relationship Between Concentration and The Accuracy of Badminton Long Serve Shots - Junanda, Hendya Alif (Journal of Physical and Outdoor Education, 2025)
This study aims to determine the level of long service skills in playing badminton for class X students of SMA Negeri Ngamprah. In doing a service stroke, concentration is needed so that there are no mistakes that result in the loss of points, concentration is something that badminton players must pay attention to. The population used in this study were class X students totaling 52 people. the sampling used was purposive sampling with a sample size of 21 people. The results of the research from the results of simple correlation data analysis obtained the correlation value between concentration and confidence with long service ability (r) is 0.821. This shows that there is a strong relationship between concentration and long service ability. It is concluded that there is a significant relationship between concentration and long service ability in class X students of SMAN 1 Ngamprah.